The Evangelical Christians-Baptists: between the religious tradition of Russia and foreign influence - Pełczyński, Grzegorz (Człowiek i Społeczeństwo, 2016)
Evangelical Christians and Baptists are Evangelical denominations representing Protestant beliefs in Russia. They share a similar approach to doctrinal matters and at one point in history united into a single ecclesiastical organisation. Domestic factors, in particular, as well as foreign influences played an important role in the Russian origins of Evangelical groups, which contributed to the Evangelical movement’s religious inquisitiveness, spiritual fervour, and readiness for martyrdom around the world. In order to develop a thorough understanding of Evangelical Christians and Baptists in Russia, one needs to explore their political and cultural backgrounds.